the equation of a circle with center (h,k) and radius r is
[tex](x-h)^2+(y-k)^2=r^2[/tex]
convert it to that form by comleting the square for the x and y terms
or, we can just expand what we know
expand [tex](x-a)^2+(y-b)^2=m^2[/tex] and make it equal to 0
so expanding we get
[tex]x^2-2ax+a^2+y^2-2by+b^2=m^2[/tex]
minus m^2 from both sides
[tex]x^2-2ax+a^2+y^2-2by+b^2-m^2=0[/tex]
arranging in decreasing power order with m² at the end
[tex]x^2+y^2-2ax+-2by+a^2+b^2-m^2=0[/tex]
that is option A
answer is A